Pengaruh Lokasi dan Harga terhadap Keputusan Pembelian di Farmers di Wilayah Cianjur, Jawa Barat - Nurjaya Nurjaya; Rahmat Taufiq Dwi Jatmika; Uus Ahmad Husaeni; Dadang Yudih (Jurnal Tadbir Peradaban, 2021)
This study aims to determine the effect of location and price on purchasing decisions at Farmers in the Cianjur Region, West Java. The method used is explanatory research with analytical techniques using statistical analysis with regression, correlation, determination and hypothesis testing. The results of this study that location has a significant effect on purchasing decisions by 46.1%, hypothesis testing is obtained t count > t table or (8.959 > 1.986). Price has a significant effect on purchasing decisions by 36.5%, hypothesis testing is obtained t count > t table or (7.343 > 1.986). Location and price simultaneously have a significant effect on purchasing decisions with the regression equation Y = 12,541 + 0,425X1 + 0,424X2 and the contribution of influence is 55.5%, hypothesis testing is obtained F count > F table or (57.897 > 2,700).